2016
DOI: 10.1103/physrevx.6.041008
|View full text |Cite
|
Sign up to set email alerts
|

Wave-front Transformation with Gradient Metasurfaces

Abstract: Relying on abrupt phase discontinuities, metasurfaces characterized by a transversely inhomogeneous surface impedance profile have been recently explored as an ultrathin platform to generate arbitrary wave fronts over subwavelength thicknesses. Here, we outline fundamental limitations of passive gradient metasurfaces in molding the impinging wave and show that local phase compensation is essentially insufficient to realize arbitrary wave manipulation, but full-wave designs should be considered. These findings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(153 citation statements)
references
References 59 publications
2
135
0
Order By: Relevance
“…For this purpose, we use a synthesis method based on generalized Snell's laws which intuitively allows for arbitrary control of reflected and transmitted waves through local phase shifts at the metasurface. It should be mentioned that this synthesize method suffers in terms of power efficiency due to spurious scattering and it has been recently found that the ideal required phase shift differs from the prescription of the generalized Snell's law [77][78][79]. However, due to the 2π phase span provided by the proposed design paradigm, it can be used flexibly in more sophisticated synthesis methods to improve the efficiency of functionality.…”
Section: Wavefront Engineering Of Generated Frequency Harmonicsmentioning
confidence: 99%
“…For this purpose, we use a synthesis method based on generalized Snell's laws which intuitively allows for arbitrary control of reflected and transmitted waves through local phase shifts at the metasurface. It should be mentioned that this synthesize method suffers in terms of power efficiency due to spurious scattering and it has been recently found that the ideal required phase shift differs from the prescription of the generalized Snell's law [77][78][79]. However, due to the 2π phase span provided by the proposed design paradigm, it can be used flexibly in more sophisticated synthesis methods to improve the efficiency of functionality.…”
Section: Wavefront Engineering Of Generated Frequency Harmonicsmentioning
confidence: 99%
“…[27] see also Ref. [36] where almost perfect absorption is demonstrated by exciting a single near-field mode).…”
Section: Introductionmentioning
confidence: 96%
“…However, in this case the wave impedance of a scattered wave does not equal to the wave impedance of an incident wave. It makes the efficiency of the anomalous reflection (refraction) to decrease significantly when the angle between the incident and reflected (refracted) wave increases (as well as the impedance mismatch) [31,35,36]. The outcome is even worse when it comes to the conversion of a propagating wave into a surface wave using the recipe provided by the generalized Snell's law.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, a theoretical scheme for gradient (spatially dispersive) metasurfaces, which offers a perfect control of refracted/reflected waves (i.e., 100% power efficiency), was introduced in the seminal studies in Refs. [3,19,21]. Based on that scheme, metasurface designs several interesting applications involving wavefront control were proposed (see e.g., Refs.…”
Section: Introductionmentioning
confidence: 99%